Aneurysm Location Affects Clinical Course and Mortality in Patients With Subarachnoid Hemorrhage - Göttsche, Jennifer; Piffko, Andras; Pantel, Tobias F.; Westphal, Manfred; Dührsen, Lasse; Czorlich, Patrick; Sauvigny, Thomas (Frontiers in Neurology, 2022)
Objective: The influence of preexisting factors on the clinical course of patients with subarachnoid hemorrhage (SAH), such as patient age, arterial hypertension, and aneurysm characteristics, is still a matter of debate. However, the specific impact of the exact aneurysm location has not received adequate attention. Therefore, aim of this study was to investigate the influence of aneurysm location as a preexisting factor on the clinical course and on mortality. Methods: Data of consecutive patients with aneurysmal SAH treated from October 2010 to July 2020 were retrospectively analyzed. Four aneurysm locations were distinguished: Anterior complex, internal carotid artery (ICA), middle cerebral artery (MCA), and posterior circulation. Logistic regression analysis and receiver operating characteristics were used to investigate the influence of aneurysm location on the occurrence of acute hydrocephalus, Delayed Cerebral Ischemia (DCI), neurological outcome and in-hospital mortality. Results: A total of 603 patients were included in this study. Patients with MCA aneurysms were 2.55 times less likely to develop acute hydrocephalus compared to patients with anterior complex aneurysms (p<0.001). DCI occurred most frequently in patients with an anterior complex aneurysm and least frequently in MCA aneurysms (p=0.003). In ICA aneurysms, mortality was 2.56-fold higher than in patients with aneurysms of the anterior complex (p=0.006). An additional ROC analysis showed a good prediction for in-hospital mortality when taking aneurysm location into account (AUC 0.855 (CI 0.817 – 0.893)). Conclusions: Aneurysm location proved to be a significant predictor of acute hydrocephalus, DCI and in-hospital mortality demonstrating the impact of this preexisting biological factor on the course of SAH.